Introduksi dan Pelatihan Pembuatan Nata de Citrullus dari Kulit Semangka untuk Mendukung Pengembangan Usaha Nata di Kota Prabumulih - Lidiasari, Eka; Widowati, Tri Wardani; Putri, Trisna Wahyu Swasdiningrum; Syafutri, Merynda Indriyani; Syaiful, Friska; Ichsan, Onne Akbar Nur; Prayitno, Citra Pratiwi (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Prabumulih has many small and medium enterprises (SMEs) whose main product is nata de coco, but the limited availability of coconut water has encouraged the development of nata de citrullus made from watermelon rind as an alternative raw material for product diversification and waste reduction. This community service activity was carried out at KsP SME and Triliyat SME through preparatory activities, outreach, hands-on training, organoleptic testing, and evaluation. Two variants were tested: a mixed extract of albedo and rind, and an albedo-only extract. Hedonic and hedonic quality tests showed that the mixed variant was preferred, with a cloudy white color and chewy texture (color scores 1.8–1.9; texture 1.5–2.1). The average hedonic scores for color and texture were 3.2 and 2.8 for the mixed variant, and 2.5 and 2.4 for the albedo variant. Pre-test and post-test evaluations showed a 57.50% increase in participants’ understanding, indicating that the training was effective and practical in supporting nata product development in SMEs.